2019
DOI: 10.1590/2447-536x.v25i3.2037
|View full text |Cite
|
Sign up to set email alerts
|

Germination and survival of Aechmea gamosepala on different substrates

Abstract: The State of Parana is one of the Brazilian regions with the highest incidence of extraction of bromeliads, among the factors for the occurrence of this situation, they highlight a great demand for this species as ornamental flowers and the easy access to forests, few cultivation ponds and difficulties for farmers in cultivation processes, especially in the early stages of cultivation. The species Aechmea gamosepala Wittmack stands out among the species of this group of ornamental plants (Bromeliaceae) with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Bromeliads are widely appreciated around the world as ornamental plants due to the diversity of shapes and colors of their flowers, inflorescences and leaves, and high durability of flowers (Anacleto, Roveda, & Ramos, 2019;Andrade-Santos et al, 2020). Besides this, recent studies have demonstrated the beneficial effects of using extracts of bromeliads in traditional medicine, with different pharmacological applications (Rathnavelu, Alitheen, Sohila, Kanagesan, & Ramesh, 2016;Espejel-Nava et al, 2020;Gollo et al, 2020;Pérez-López et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bromeliads are widely appreciated around the world as ornamental plants due to the diversity of shapes and colors of their flowers, inflorescences and leaves, and high durability of flowers (Anacleto, Roveda, & Ramos, 2019;Andrade-Santos et al, 2020). Besides this, recent studies have demonstrated the beneficial effects of using extracts of bromeliads in traditional medicine, with different pharmacological applications (Rathnavelu, Alitheen, Sohila, Kanagesan, & Ramesh, 2016;Espejel-Nava et al, 2020;Gollo et al, 2020;Pérez-López et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, bromeliads have been appreciated as ornamental plants, especially in the USA, Europe, and Australia, where their growth is responsible by the important economy, absorbing, directly or indirectly, a large amount of labor (Paula and Silva, 2004). In this scenario, it is noteworthy that bromeliads have dozens of new species inserted in the ornamental plant trade annually (Pulido et al, 2018;Negrelle and Anacleto, 2019;Anacleto et al, 2019). In general, any plant can have ornamental use, if it fits the environment to be decorated and that meets the purpose of use, either in internal or external gardens (Tombolato, 2008).…”
Section: Introductionmentioning
confidence: 99%